First report on the Olethreutini (Lepidoptera: Tortricidae: Olethreutinae) of Lao PDR with descriptions of two new species - Pinkaew, Nantasak; Phewphanh, Phonepadith (Zootaxa, 2017)
We present the results of the first study of the tortricid moths of Lao PDR (Laos), with this report focusing on the tribe Oleuthreutini. We report 27 species from Laos for the first time, including two that are described as new: Diakonoffiana laosensis Phewphanh and Pinkaew, n.sp., and Lobesia acicula Phewphanh and Pinkaew, n.sp. As is typical of many inventories, over half of the species (i.e., 15) were documented by a single specimen.